Faktor-faktor Kebolehan al-Mubtada berupa Isim Nakirah dalam Kajian Ilmu Nahwu - Mahmuddin, Ronny (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2018)
One of the subjects in the study of Nahwu Knowledge is al-Mubtada. AlMubtada is one of the important elements in a sentence. One cause of imperfect sentence is due to unfamiliarity with al-Mubtadaâ€™ and the absence of al-Mubtadaâ€™. Beginner students in studying Nahwu only understand that al-Mubtada has to be in a form of Ism Maâ€™rifah and not in a form of Ism Nakirah. However, if it is further analyzed, al-Mubtada in a form of Ism Nakirah can be found. Therefore, the author of this paper attempted to explain about â€œConditions on al-Mubtada in a form of Ism Nakirah in the study of Nahwu knowledgeâ€. Before explaining further on this subject, the author previously mentioned definitions of al-Mubtada, kinds of al-Mubtada, and the grammar of al-Mubtada. Therefore, the readers may achieve comprehensive understanding of al-Mubtada in the study of Nahwu Knowledge. This paper is analyzed by applying literature method.